Analisis Faktor Perubahan Tingkat Upah Dan Modal Kerja Perusahaan Serta Implikasinya Terhadap Penyerapan Tenaga Kerja Sektor Industri Non Formal Di Kabupaten Batubara: Studi Pada Usaha Kontraktor Perdagangan Umum PT. Tindo Jaya Mitra - Permana, Fikri Agam; Suwadi, Suwadi; Candrasa, Limega (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to determine the factor analysis of changes in the level of wages and working capital of the company and its implications for the absorption of labor in the non-formal industrial sector in Batubara Regency. It can be concluded that the first hypothesis proposed states that the Wage Level variable (X1) has an effect on the Labor variable (Y). The second hypothesis proposed states that the working capital variable (X2) has no effect on the labor variable (Y). The fourth hypothesis proposed states that the Wage Level Variable (X1), Working Capital Variable (X2), has a significant effect simultaneously (simultaneously) on the Labor Variable (Y).